2000
DOI: 10.1046/j.1365-2885.2000.00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Single‐dose pharmacokinetics of flumequine in cod (Gadus morhua) and goldsinny wrasse (Ctenolabrus rupestris)

Abstract: Knowledge of the pharmacokinetic properties of drugs to combat bacterial infections in cod (Gadus morhua) and wrasse (Ctenolabrus rupestris) is limited. One antimicrobial agent likely to be effective is flumequine. The aim of this study was to investigate the pharmacokinetic properties of flumequine in these two species. Flumequine was administered intravenously to cod (G. morhua) at a dose of 5 mg/kg bodyweight and wrasse (C. rupestris) at a dose of 10 mg/kg. Flumequine was also administered orally to both sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 19 publications
4
22
0
Order By: Relevance
“…Tissue and plasma analysis showed that flumequine was readily absorbed and distributed from plasma to tissues (Table 1). This confirmed the results obtained by Hansen & Horsberg (2000), who calculated the volume of distribution (V d ) of flumequine in cod to be 2.4 l kg -1 following a single bolus intravenous administration. In the same study, a plasma C max of 3.5 µg ml -1 was found 24 h after a single oral administration of 10 mg kg -1 body weight.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Tissue and plasma analysis showed that flumequine was readily absorbed and distributed from plasma to tissues (Table 1). This confirmed the results obtained by Hansen & Horsberg (2000), who calculated the volume of distribution (V d ) of flumequine in cod to be 2.4 l kg -1 following a single bolus intravenous administration. In the same study, a plasma C max of 3.5 µg ml -1 was found 24 h after a single oral administration of 10 mg kg -1 body weight.…”
Section: Discussionsupporting
confidence: 90%
“…In that respect several authors, including the corresponding author of this paper, related pharmacokinetic data of antibacterial agents in fish to the assumptions by Stamm (1989) and Shojaee AliAbadi & Lees (2000) with the aim of predicting clinical outcome of the treatment. Taking the plasma C 24 concentrations found in this study, a MIC value of 0.015 µg ml -1 determined by Samuelsen & Lunestad (1996) and a calculated AUC value of 533 mg h l -1 for flumequine in cod (Hansen & Horsberg 2000) in combination with the statements by Stamm (1989) and Shojaee AliAbadi & Lees (2000), it can be shown that all the doses of flumequine used in the present study fulfil the criteria (Table 1). A plot of the mean plasma concentrations against doses, excluding the 10 mg dose, shows a linear relationship (Fig.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations